2020
DOI: 10.1038/s41598-020-68476-3
|View full text |Cite
|
Sign up to set email alerts
|

Munc18-1 induces conformational changes of syntaxin-1 in multiple intermediates for SNARE assembly

Abstract: In neuronal exocytosis, SNARE assembly into a stable four-helix bundle drives membrane fusion. Previous studies have revealed that the SM protein Munc18-1 plays a critical role for precise SNARE assembly with the help of Munc13-1, but the underlying mechanism remains unclear. Here, we used single-molecule FRET assays with a nanodisc membrane reconstitution system to investigate the conformational dynamics of SNARE/Munc18-1 complexes in multiple intermediate steps towards the SNARE complex. We found that single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Therefore, during SNARE complex assembly, the syntaxin/Munc18 complex requires a brain-specific priming factor, such as Munc13-1, to catalyze the transition of the Habc domain of syntaxin to an open conformation, exposing the C-terminal SNARE motif and allowing for the initiation of SNARE complex formation in the presence of SNAP-25 and synaptobrevin 15, 16, 18, 20 . Recent single-molecule fluorescence studies have demonstrated the conformation of isolated syntaxin-1a in a dynamic transition between an open and closed conformation, despite the complete closed conformation seen by NMR and SAXS data 15, 17, 21, 24, 40, 41 . Despite the importance of the conformational switch of syntaxin in controlling synaptic vesicle exocytosis, the underlying molecular mechanism of other isoforms has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, during SNARE complex assembly, the syntaxin/Munc18 complex requires a brain-specific priming factor, such as Munc13-1, to catalyze the transition of the Habc domain of syntaxin to an open conformation, exposing the C-terminal SNARE motif and allowing for the initiation of SNARE complex formation in the presence of SNAP-25 and synaptobrevin 15, 16, 18, 20 . Recent single-molecule fluorescence studies have demonstrated the conformation of isolated syntaxin-1a in a dynamic transition between an open and closed conformation, despite the complete closed conformation seen by NMR and SAXS data 15, 17, 21, 24, 40, 41 . Despite the importance of the conformational switch of syntaxin in controlling synaptic vesicle exocytosis, the underlying molecular mechanism of other isoforms has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Munc18-1 exclusively orchestrate the assembly of release machinery [21]. Evidence from previous studies in neuroendocrine cells suggest the two proteins colocalize at docked vesicles and disperse following vesicular neurotransmitter release [22][23][24][25].…”
Section: Assessing Colocalization Of Synaptic Release Proteinsmentioning
confidence: 95%
“…The N-terminal peptide is essential for vesicle fusion itself, whilst the Habc domain regulates this fusion by forming a closed syntaxin-1 conformation ( 20 , 21 ). The current hypothesis is that Munc18-1 and syntaxin-1 have several binding modes: i) Munc18-1 binds to syntaxin-1 (via the Habc domain) in a ‘closed’ conformation, stabilizing the conformation of syntaxin-1 and inhibiting the assembly of the SNARE complex ( 16 ); ii) Munc18-1 combined with ‘closed’ conformation syntaxin-1 serves as a template for SNARE assembly, with Munc13-1 helping to open the syntaxin-1 ‘closed’ conformation. Munc13-1 Bridges synaptic vesicles and presynaptic membrane fusion, and Munc18-1 and Munc13-1 coordinate the assembly of the T-SNARE complex together in an NSF-SNAP resistant manner ( 22 ); and iii) Munc18-1 combined with the ‘open’ conformation ofsyntaxin-1 (N-terminal short peptide) initiates and stimulates SNARE-mediated membrane fusion ( 16 ).…”
Section: Function Of Munc18-1mentioning
confidence: 99%
“…The current hypothesis is that Munc18-1 and syntaxin-1 have several binding modes: i) Munc18-1 binds to syntaxin-1 (via the Habc domain) in a ̔closed̓ conformation, stabilizing the conformation of syntaxin-1 and inhibiting the assembly of the Snare complex (16); ii) Munc18-1 combined with ̔closed̓ conformation syntaxin-1 serves as a template for Snare assembly, with Munc13-1 helping to open the syntaxin-1 ̔closed̓ conformation. Munc13-1 Bridges synaptic vesicles and presynaptic membrane fusion, and Munc18-1 and Munc13-1 coordinate the assembly of the T-Snare complex together in an nSF-SnaP resistant manner (22); and iii) Munc18-1 combined with the ̔open̓ conformation ofsyntaxin-1 (n-terminal short peptide) initiates and stimulates Snare-mediated membrane fusion (16). The regulatory mechanism of Munc18-1 is complex, involving promotion and inhibition of Snare assembly; however, the promotion process is the more dominant of the two.…”
Section: Function Of Munc18-1mentioning
confidence: 99%
See 1 more Smart Citation